Experimental Analysis of a Gantry Crane of a Shell Structure - Bagusław ŁADECKI; Sławomir BADURA; Filip MATACHOWSKI (Engineering Transactions)
Gantry cranes of the shell structure are used in Polish steel industry much less than other gantry crane types. Those gantry cranes characterized by increased susceptibility to mechanical vibrations, resulting in greater sensitivity to the formation of fatigue cracks. In this work, measurements of strain gauge bridge deformation of the shells, for which periodically conducted non-destructive testing revealed the presence of numerous fatigue cracks mainly in the area of the under rail beams. Performed periodically repair and reinforcement of the crane did not eliminate the problem of the formation of the subsequent fatigue cracks. The analysis of the dynamic operation of the bridge, in combination with FEM calculations carried out showed stresses exceeding the limit value due to the fatigue phenomena. The results of dynamic analysis can serve as a basis to perform more accurate analysis of the fatigue life of the most intensive areas of the bridge.